Current-mode multiphase sinusoidal oscillator based on log-domain filtering - Prommee, Pipat; Somdunyakanok, Montri (My University, 2010)
This paper describes the design of a multiphase sinusoidal oscillator (MSO) based on log-domain filtering concept. The circuit is a direct realization of a first-order differential equation for obtaining the inverting lossy integrators. Each integrator comprises only a grounded capacitor and four transistors per phase. The proposed MSO can be instantaneously controlled over a very wide frequency range by controlling a current for oscillation frequency and oscillation condition which are indicated proposed MSO suitability in high-frequency communications. The power consumption is obtained around 5.5mW at 100μA of bias current based on 2.5V single power supply. The oscillation frequency is controlled over four decades of frequency. The total harmonic distortion of three-phases (11.5MHz) is obtained around 2.4%.
Keywords: Electronically-controlled; High-frequency; Log-domain filtering; Low-voltage; Multiphase sinusoidal oscillator